The hepaticae of West Greenland from ca. 66°N to 72°N. - Schuster, R. M.; Damholt, K. (Meddelelser om Grønland, 1974)
This work, the result of two seasons intensive field work and of many months of microscopic study of the collected materials, represents an in-depth taxonomic and ecological study of the Hepaticae known to occur in West Greenland (from 66° to ?2° N). It is based primarily on study of living plants and, as such, is the most comprehensive study of Arctic H epaticae ever undertaken; in addition a large mass of herbarium material from the Botanical Museum of Copenhagen has been examined as well as various early collections (in part of BERGGREN, housed at Lund). The emphasis on study of living plants is unique and allows formation of taxonomic judgments which a study based on dead (herbarium) materials would not allow. Several new species are described and many taxa are here first reported for Greenland. Detailed study of phenotypic variation of various critical taxa has made possible a clearer understanding of these plants. In difficult groups keys are provided and illustrative matter provided (where it supplements or complements the illustrations found in the senior author’s The Hepaticae and Anthocerotae of North America, Vols. 1-111, Columbia University Press). Distribution maps showing the regional range are provided, and an introductory general section giving historical and environmental perimeters of the study.